Satisfaction among hospital staff nurses on nurse staffing calculation-performance-oriented calculation based on Indonesian National Nurses Association (INNA) on information system - Rani Kawati Damanik; Adventy Riang Bevy Gulo (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: The Indonesian National Nurses Association (INNA) has a method and tool for staffing calculation-performance-oriented calculation based on information systemPurpose: To identify of satisfaction among hospital staff nurses on nurse staffing calculation-performance-oriented calculation based on Indonesian National Nurses Association (INNA) on information systemMethod: The technique of determining the sample using the Cohen effect size (d) formula, the total sample is 30 nurses, divided by two groups, each group comprise 15 nurses the as control group and intervention group 15. The pre-post test done for both groups. The training given to participants for two days and following by measured to identify of satisfaction among hospital staff nurses twice to control and intervention groups using a questionnaire.Results: The Kolmogorov Smirnov normality test and finding the data had abnormally distributed (p <0.05), and following by the Mann Whitney test. The results showed that all the participants showed an increase in nurse satisfaction on nurse staffing calculation-performance-oriented calculation based on Indonesian National Nurses Association (INNA)Conclusion: There is a difference in the level of satisfaction between a control group and an intervention with a range of 4.66 points. Using nurse staffing calculation-performance-oriented calculation based on Indonesian National Nurses Association (INNA) on information system, it applicable and reasonable to nurses to calculate nurse staffing in the hospital.